PENGGUNAAN ZAT WARNA ORGANIK UNTUK MENINGKATKAN PERFORMA PERALATAN SOLAR CELL MENGGUNAKAN METODA DENSITY FUNCTIONAL THEORY (DFT) (Lantanida Journal, 2017)
To improve the performance of solar cell equipment can be used dye as a sensitizer, a sensitizer role is to help absorb visible light in equipment that uses a semiconductor with a wide band gap such as TiO2 and ZnO . The calculation methods used are computationally DFT and TD - DFT to determine the value of geometry optimization , energy , population density and optical properties . As for knowing the performance of experimental equipment can be obtained from the value of the open circuit voltage ( Voc ) , short circuit current density (Jsc), Fill Factor. The dye can be enhanced sensitivity capabilities with the engineering structure or conformation of the molecule.
Keywords: Dye; Solar cell; Density functional theory.